Boganmeldelser - Inger Dübeck; Georg Høyer; Alvar Nelson; Henrik Stevnsborg; Beth Grothe Nielsen; Marja Taussi Sjöberg; Leif Petter Olausson; Hans Klette; K. J. Lång (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews